1996
DOI: 10.1021/jo960296k
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 4,4-Disubstituted β-Lactams by Regiospecific Electrophile- and Silver-Induced Ring Expansion of 2,2-Disubstituted 1-Methoxycyclopropylamines

Abstract: 2,2-Disubstituted 1-methoxycyclopropylamines underwent regiospecific ring expansion to 1,4,4-trisubstituted 2-azetidinones by N-chlorination with tert-butyl hypochlorite and subsequent rearrangement with silver tetrafluoroborate. Upon thermolysis, 4,4-disubstituted beta-lactams suffer a characteristic ring opening to afford beta,gamma-unsaturated carboxylic amides. The reduction of 1,4,4-trisubstituted 2-azetidinones with lithium aluminum hydride afforded 1,2,2-trisubstituted azetidines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 30 publications
1
21
0
Order By: Relevance
“…While in organic chemistry much of the effort involving the azetidine nucleus has been directed to its synthesis, few examples of rearrangements of the azetidine ring are known. Dialkyl azetidines afford olefins through a Hoffmann type elimination . Amino alcohols have been obtain by hydrogenolysis of 4-arylazetidines, as well as from bis-azetidines …”
Section: Resultsmentioning
confidence: 99%
“…While in organic chemistry much of the effort involving the azetidine nucleus has been directed to its synthesis, few examples of rearrangements of the azetidine ring are known. Dialkyl azetidines afford olefins through a Hoffmann type elimination . Amino alcohols have been obtain by hydrogenolysis of 4-arylazetidines, as well as from bis-azetidines …”
Section: Resultsmentioning
confidence: 99%
“…375,377,378,379,380 Typically, the N-chloroamines are obtained by N-chlorination of cyclopropane hemiaminals, which are prepared by the addition of amines onto cyclopropanone derivatives, and are then directly treated with silver(I). 375,377,378 This one-pot procedure has been applied to the In contrast, the reported ring-opening reactions of N-chlorocyclopropylamines substituted with a phenyl or a carboxylic acid group at the α position relative to the nitrogen atom yield linear products in the presence of methanol or water.…”
mentioning
confidence: 99%
“…With general access to aw ide variety of highly reactive cyclopropanone precursors,w es ought to apply these substrates in strain-releasing rearrangements.C onsidering the biological relevance of b-lactam derivatives, [25] ap articularly attractive transformation we were prompted to study is the formal [3+ +1] cycloaddition of cyclopropanones with nitrene equivalents to afford b-lactams.A na nalogous Schmidt-type rearrangement had previously been reported by AubØ and coworkers using (1-ethoxycyclopropoxy)trimethylsilane in the presence of organoazides and BF 3 •OEt 2 , [26] although only unsubstituted achiral b-lactam derivatives could be obtained in low to moderate yield. [27,28] In that work, the relatively harsh conditions required for equilibration to cyclopropanone likely led to multiple decomposition pathways.Moreover,we sought to avoid organoazides in order to improve the applicability of the method on alarger scale.After evaluating various other nitrene equivalents, [11] it was found that simple hydroxylamines or their corresponding ethers could play the same role when the reaction was run in presence of aL ewis acid (Scheme 4). Indeed, treatment of ac hosen hydroxylamine with the 1-sulfonylcyclopropanol substrate leads to smooth formation of astable hemiaminal intermediate under mild basic conditions,w hich then rearranges in situ to the corresponding b-lactam following addition of Al(OTf) 3 .…”
Section: Synthesis Of B-lactams By Formal [3+ +1] Cycloadditionmentioning
confidence: 99%